Correlation of urinary nephrin with albuminuria as early marker of diabetic nephropathy in type 2 diabetes mellitus - Amiruzzaman, Md.; Islam, Moinul; Prasad, Indrajit (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Diabetic nephropathy (DN) is a leading cause of end-stage renal disease and a public health concern nowadays. Early detection is imperative to halt the progression. Albuminuria has been considered a gold standard for early detection of DN, but it has several limitations. Nephrin is a podocyte-specific protein and a key structural element of the glomerular filtration barrier, which has been considered a promising early marker of DN. Objectives: To determine the correlation of urinary nephrin with albuminuria as an early marker of diabetic nephropathy in type 2 DM. Methods: This case-control study was performed from July 2023 to December 2024. A total of 86 participants were recruited purposively and allocated into four groups. Group A comprised non-diabetic healthy individuals, while the other three groups consisted of people with type 2 DM, categorized into Group B (normoalbuminuria), Group C (microalbuminuria), and Group D (macroalbuminuria). Informed written consent was taken. History, clinical evaluation, and laboratory investigations, including UACR, urinary nephrin, s. creatinine, urine R/M/E, HbA1C, FPG, and PPG were done. SPSS version 26.0 was used for statistical analysis. P-value <0.05 was considered significant. Result: Urinary nephrin increased progressively and significantly across the group and showed significant positive correlations with HbA1C & UACR and a negative correlation with eGFR. It has a very high and significant odds ratio of 116.83. ROC curve of urinary nephrin revealed AUC 0.977 (≥0.75 ng/ml) with 92.16% sensitivity and 90.91% specificity for predicting DN. It was 100% positive among diabetes with micro or macroalbuminuria, and 76.19% positive in those with normoalbuminuria. Conclusion: Urinary nephrin revealed a significant positive correlation with UACR in people with type 2 DM. Even in the normoalbuminuria stage, its significant positivity suggests that it could be a more reliable early predictive marker of diabetic nephropathy than UACR. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S46]